The effect of dramatic play on early literacy: an experimental study - Aslan, Fatih Mehmet; Yüzbaşıoğlu, Yasemin; Alptekin, Ayşe; Sarıkaya, Ayşegül (Institute of Advanced Engineering and Science, 2025)
In line with the theories of Piaget and Vygotsky, the aim of the present study is to examine the effect of the dramatic play activities program on the early literacy skills of preschool children. The study is based on an experimental research design with pretest-posttest and control group. While the dependent variable of the study is children’s early literacy skills, the independent variable is dramatic play activity. Early literacy test (EROT) was used as data collection tool. The participants of the present study consist of 32 children divided equally as the participants of the experimental and control group. The age of the children is between 63-72 months. The children in the experimental group participated in a program of dramatic play activities over a period of 10 weeks, 5 days each week, 2 hours daily for 100 hours in total. Analysis of covariance (ANCOVA), t-test, and descriptive statistics were used in the analysis of the data. In line with the data obtained in the present study, dramatic play activity program positively affects the early literacy skills of preschool children in terms of receptive language and expressive language vocabulary acquisition, naming skills, functional knowledge, and listening comprehension skills.